A study of universal values of sports in high schools based on ethnicity - Ali, Burhan; Gumilar, Agus; Martini, Tri (Jurnal Patriot, 2024)
Problems: Sports in high school are not just physical exercise; they also teach values that will shape students' behavior and personalities in the future. Sports shape one's character and ethics significantly through teaching universal values such as discipline, sportsmanship, honesty, and teamwork. Due to its diverse ethnic population, Indonesia faces its own difficulties in incorporating the universal values of sports into its education system. Purpose: Therefore, it is important to conduct research on the universal values of sports at the high school level from an ethnic perspective to understand the socio-cultural dynamics that occur in Indonesia. Methods: The research instrument used was a questionnaire. The study involved 261 high school student respondents, consisting of 97 Lampung ethnicities and 164 non-Lampung ethnicities, aged between 14 and 18 years. The instrument was to measure the universal values of sport, which consisted of six assessed components. Results: Analysis of the Mann-Whitney u test showed that the sig (2-tailed) value of 0.325 was greater than 0.05, indicating that there was no significant difference in the distribution of universal sports values between the two ethnic groups Lampung and Non-Lampung. Conclusion: Following up on the findings of this study, diverse cultural perspectives are essential for educational programs and approaches objectives, methods, and research results.